Insights into APC/C: from cellular function to diseases and therapeutics. Issue 1 (March 2016) - Zhou, Zhuan; He, Mingjing; Shah, Anil; Wan, Yong
Abstract Anaphase-promoting complex/cyclosome (APC/C) is a multifunctional ubiquitin-protein ligase that targets different substrates for ubiquitylation and therefore regulates a variety of cellular processes such as cell division, differentiation, genome stability, energy metabolism, cell death, autophagy as well as carcinogenesis. Activity of APC/C is principally governed by two WD-40 domain proteins, Cdc20 and Cdh1, in and beyond cell cycle. In the past decade, the results based on numerous biochemical, 3D structural, mouse genetic and small molecule inhibitor studies have largely attracted our attention into the emerging role of APC/C and its regulation in biological function, human diseases and potential therapeutics. This review will aim to summarize some recently reported insights into APC/C in regulating cellular function, connection of its dysfunction with human diseases and its implication of therapeutics.